2015
DOI: 10.1080/10911359.2014.976697
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Judgment and Behavior Toward Women Wearing High Heels

Abstract: Research has consistently shown that the appearance of women's apparel influences men's behavior and judgment. However, the effect of women's shoe heels has received little interest. Female confederates wearing black shoes with 0-, 5-, or 9-cm heels walked on the street. In a first experiment, we examined the number of men in the street who smiled at the female confederate. More smiles were addressed to the confederate with high heels. In a second experiment, the confederates asked men and women to respond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…Such results are in line with the findings reported by Guéguen (2015) and Guéguen and Stefan (2015) who observed in several studies that men approached a woman wearing high heels more readily. Our results were also congruent with the findings of Morris et al (2013) who reported that women wearing high heels were perceived as more feminine.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Such results are in line with the findings reported by Guéguen (2015) and Guéguen and Stefan (2015) who observed in several studies that men approached a woman wearing high heels more readily. Our results were also congruent with the findings of Morris et al (2013) who reported that women wearing high heels were perceived as more feminine.…”
Section: Resultssupporting
confidence: 93%
“…Thus, overall, these new findings expand those reported by Morris et al (2013), Guéguen (2015), and Guéguen & Stefan (2015). We also found that the legs and the buttocks of the woman were perceived more positively when she was wearing high heels.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The high-heeled shoes were a particularly noteworthy aspect of this performance because they are at once a signifier of vulnerability and abilityto balance and display physical form, not unlike Nyamza en pointe. 43 How women are expected to perform their female attractiveness is often defined, and policed, by the media, magazines, and society at large.…”
Section: Memala Nyamza: Hatchedmentioning
confidence: 99%